Edukasi Publik Literasi Keuangan Berbasis Pengabdian Mahasiswa KKN Desa Manik Maraja: Menanamkan Pemahaman Investasi Sejak Dini bagi Siswa SMA YPI Dharma Budi - Ardhi Sahjaya; M Rizky Erlangga; Muhammad Ikhsan Harahap; Siti Aisyah (STARLA: Jurnal Pengabdian Masyarakat, 2026)
The low level of financial literacy among Generation Z in Indonesia has become a serious concern, particularly in rural areas such as Manik Maraja Village. This Community Service (PKM) activity was carried out by students of the Real Work Lecture (KKN) program at Universitas Islam Negeri Sumatera Utara in response to this situation, involving 152 students of SMA YPI Dharma Budi on August 14, 2025. This study employed a descriptive qualitative approach with a pre-post assessment design to measure participants’ understanding before and after the educational intervention. The theoretical framework used includes financial literacy theory (Lusardi & Mitchell, 2014), the Service-Learning model (Eyler & Giles, 1999), and Social Learning Theory (Bandura, 1977). The activity adopted participatory education methods comprising three main components: material presentation by a resource person from the Indonesia Stock Exchange (IDX) Representative Office of North Sumatra, interactive discussion, and a question-and-answer session. Pre-test results showed a mean initial comprehension score of 38.4 (scale of 100), while post-test results reached 71.6, indicating an improvement of 33.2 points (86.5%). A total of 87.5% of participants expressed interest in beginning to invest in the sharia capital market. The activity proved effective in improving students’ financial literacy and is recommended as a replicable thematic KKN program model for villages with similar characteristics.